2012
DOI: 10.1055/s-0040-1703597
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Perspectives on Health and Illness

Abstract: Introduction: Every society has its own traditional beliefs and practices related to health care. Some practices are effective whereas others may be harmful or ineffective. These beliefs and practices are linked to culture, environment and education. Health workers must have concern for the community's cultural values and beliefs so that they can utilize the harmless practices for effective use as well as eliminate harmful practices. Objectives of the study were to explore the adults perception on health and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In the study, a common form of self-treatment involved the use of herbs and over-the-counter drugs. It seems that the results are congruent with the results of other studies ( 29 - 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the study, a common form of self-treatment involved the use of herbs and over-the-counter drugs. It seems that the results are congruent with the results of other studies ( 29 - 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…Utilization management models focus on decisions and processes that manage healthcare costs on an individual case basis to reduce waste and unnecessary service and product use while also identifying cost-effective and necessary interventions that provide the most effective outcome (quality) [10,11]. Socio-cultural models took into consideration the highly complex institutional and environmental norms along with the interpersonal perceptions embedded within an enterprise and how these dynamics impact adoption [12][13][14][15][16]. We found that these models were incomplete in addressing our specific inquiry regarding research support services and their use.…”
Section: Future Researchmentioning
confidence: 99%
“…The cultural dimension refers to behaviors and concepts particular to a given societal context; as such, they are frequently only meaningful to a certain group of people. This dimension is comprised of traditional beliefs and values (Nayak and Geroge, 2012) and religious practices such as prayer, meditation, ceremony and ritual (Charlier et al, 2017;Nayak and Geroge, 2012;Spector, 2002) which are closely related to the cultural environment within communities. Culture helps to establish a comforting and secure environment that includes such beliefs, values and practices.…”
Section: Cultural Dimensionmentioning
confidence: 99%
“…Apparently, the scope of students' concept of health fails to correspond with a holistic concept of health. Cultural issues are considered an important aspect of an overall health concept by many researchers such as Spector (2002) and Nayak and Geroge (2012) and thus cannot be neglected. However, no participants' responses touched on the cultural dimension, suggesting that no respondents in this study devoted any thought to that dimension of an overall health concept.…”
Section: Total Participants' Responsesmentioning
confidence: 99%